Secreted phosphoprotein 1 upstream invasive network construction and analysis of lung adenocarcinoma compared with human normal adjacent tissues by integrative biocomputation - Sun, Ying; Wang, Lin; Jiang, Minghu; Huang, Juxiang; Liu, Zhenqiu; Wölfl, Stefan (Cell biochemistry and biophysics, 2010)
The aim of this study is to set up single molecular secreted phosphoprotein 1 (SPP1) upstream invasive network of lung adenocarcinoma. This paper proposed an integrated method based on linear programming and a decomposition procedure with integrated analysis of the significant function cluster using Kappa statistics and fuzzy heuristic clustering. Our study proved that only modules appearing in lung adenocarcinoma include cytokine module (CXCL13, GREM1_2 inhibition), cell adhesion module (COL11A1_2 activation; CDH3 inhibition), and receptor binding module (NMU activation; CXCL13, GREM1_2 inhibition), which increase the invasion of cancer cell. We compared skeletal development, signal, biological regulation, sequence variant modules between human normal adjacent tissues and lung adenocarcinoma. SPP1 skeletal development module appears in human normal adjacent tissues (COL11A1_1 activation; COL10A1 inhibition), whereas in lung adenocarcinoma (COL11A1_2, COL1A2 activation); signal module appears in human normal adjacent tissues (COL11A1_1, CXCL13, MMP11, SPINK1 activation; COL10A1, COL3A1 inhibition), whereas in lung adenocarcinoma (COL11A1_2, COL1A2, MMP12 activation; CDH3, CXCL13, GREM1_2, MMP11, SPINK1 inhibition); biological regulation module appears in human normal adjacent tissues (CXCL13, MKI67, PYCR1 activation; NEK2, SPDEF, TOP2A_2, TOX3_1 inhibition), whereas in lung adenocarcinoma (HMGB3, MKI67, NMU, PYCR1, TOX3_2 activation; CXCL13, SPDEF, TOP2A_2 inhibition); sequence variant module appears in human normal adjacent tissues (COL11A1_1, MKI67, MMP11 activation; ASPM, COL10A1, COL3A1, NEK2, TMPRSS4, TOP2A_2 inhibition), whereas in lung adenocarcinoma (COL11A1_2, COL1A2, HMMR, MKI67, MMP12 activation; ABCC3, ASPM, CDH3, MMP11, TOP2A_2 inhibition). It can be deduced that modules above in human normal adjacent tissues reflect the invasive inhibition of normal cells, whereas in lung adenocarcinoma increase the invasion of cancer cell. Our study of SPP1 upstream invasive network may be useful to identify novel and potentially targets for prognosis and therapy of lung adenocarcinoma.
Erstmals am 01 December 2009 online veröffentlicht
Gesehen am 06.09.2023